Kiss the girls and make them cry - Clark, Mary Higgins (New York : Simon & Schuster, 2019)
"When investigative journalist Gina Kane receives an email from a "CRyan" describing her "terrible experience" while working at REL, a high-profile television news network, including the comment "and I'm not the only one," Gina knows she has to pursue the story."--provided by publisher.
A novel.
Keywords: Television broadcasting -- Employees -- Fiction; Women journalists -- Fiction; Billionaires -- Fiction; Journalists -- Fiction; Businessmen -- Fiction; Rape victims -- Fiction; Women college students -- Abuse of -- Fiction; Sexual harassment -- Fiction; Executives -- Sexual behavior -- Fiction; Thrillers (Fiction); Detective and mystery fiction